Table1_v1_Geodynamic Implications of Synchronous Norite and TTG Formation in the 3 Ga Maniitsoq Norite Belt, West Greenland.XLSX - Pedro Waterton; William R. Hyde; Jonas Tusch; Julie A. Hollis; Christopher L. Kirkland; Carson Kinney; Chris Yakymchuk; Nicholas J. Gardiner; David Zakharov; Hugo K. H. Olierook; Peter C. Lightfoot; Kristoffer Szilas (2020)
We present new data for the ∼3.0 Ga Maniitsoq Norite Belt of the Akia Terrane, West Greenland, with the aim of understanding its petrogenesis. The Maniitsoq Norite Belt is hosted in regional tonalite-trondhjemite-granodiorite (TTG) and dioritic orthogneisses, intruded by later sheets of TTG and granite pegmatites, and comprises two main rock types: plagioclase-rich “norites” and pyroxene-rich “melanorites”. Both norites and melanorites have high SiO 2 contents (52–60 wt% SiO 2 ), high bulk rock Mg# (0.57–0.83), and low TiO 2 contents (0.1–0.7 wt%). Their trace element patterns are defined by depleted heavy Rare-Earth elements, highly enriched light Rare-Earth elements, negative anomalies in Nb, Ta, and Ti, and variable anomalies in Zr, Hf, and Eu. New zircon U-Pb geochronology data and previously published ages establish an emplacement age of 3,013 ± 1 Ma for the majority of the Maniitsoq Norite Belt, with magmatism continuing until 3,001 ± 3 Ma. This ∼12 Myr period of norite magmatism is coeval with an ongoing period of TTG production in the Akia Terrane. Norite Belt emplacement was closely followed by high temperature, low pressure granulite-facies metamorphism at ∼800°C and <9 kbar. These conditions imply high temperature gradients (>900°C/GPa) and that the norite magmas were emplaced into thin crust and lithosphere. Compositions of the norites and melanorites can be explained by derivation from a single mafic parental melt (∼13 wt% MgO), with the norites predominantly accumulating plagioclase and the melanorites predominantly accumulating pyroxene. Evidence from field relationships, the presence of xenocrystic zircon, major element compositions and combined trace element and Hf-isotope modelling suggests the norites were contaminated by assimilation of ∼20–30% continental TTG crust. Geochemical and Hf-Nd isotopic constraints indicate that the norite mantle source was depleted, and that this depletion occurred significantly before the emplacement of the norite magmas. Contemporaneous production of both ...